Diabetes mellitus and the risk of bladder cancer: A PRISMA-compliant meta-analysis of cohort studies. Issue 46 (November 2017) - Xu, Yongping; Huo, Rui; Chen, Xi; Yu, Xuefeng
Abstract: Background: Epidemiologic studies have reported inconsistent results regarding the relationship between diabetes mellitus (DM) and the incidence of bladder cancer. This comprehensive systematic review and meta-analysis explored and evaluated this relationship in participants with different characteristics. Methods: Studies indexed in the PubMed, Embase, and the Cochrane Library databases that compared bladder cancer incidence mortality between DM and non-DM participants were included in the present study. The relative risks (RRs) of a random-effects model were used to assess these associations. Results: The final analysis included 21 cohort studies, involving a total of 13, 505, 643 participants. Overall, DM was associated with an increased risk of bladder cancer or cancer mortality when compared with non-DM participants (RR: 1.23; 95% confidence interval [CI]: 1.12–1.35; P  < .001). Furthermore, DM had a harmful impact on subsequent bladder cancer risk in men compared with those without DM (RR: 1.23; 95% CI: 1.06–1.42; P  = .005), whereas no significant relationship was observed between DM and bladder cancer in women (RR: 1.24; 95% CI: 0.95–1.61; P  = .119). There was no significant gender difference for this relationship (ratio of RR: 0.99; 95% CI: 0.73–1.34; P  = .958). In addition, cancer incidence (RR: 1.21; 95% CI: 1.09–1.35; P  < .001) and cancer mortality (RR: 1.25; 1.17–1.35; P  < .001) both increased in DM patients. Finally, smoking status and follow-up duration might also affect this relationship in men and women. Conclusions: The findings of this study indicated that DM was associated with elevated bladder cancer or cancer mortality risk, especially in men. This relationship in women requires further exploration. Abstract : Supplemental Digital Content is available in the text